2021
DOI: 10.1183/16000617.0182-2020
|View full text |Cite
|
Sign up to set email alerts
|

Minute ventilation/carbon dioxide production in patients with dysfunctional breathing

Abstract: Dysfunctional breathing refers to a multi-dimensional condition that is characterised by pathological changes in an individual's breathing. These changes lead to a feeling of breathlessness and include alterations in the biomechanical, psychological and physiological aspects of breathing. This makes dysfunctional breathing a hard condition to diagnose, given the diversity of aspects that contribute to the feeling of breathlessness. The disorder can debilitate individuals without any health problems, but may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 34 publications
1
36
0
1
Order By: Relevance
“…This increase is accomplished by increases in both the tidal volume and breathing frequency. During low-to-moderate intensity exercise, both tidal volume and breathing frequency increase roughly in proportion to exercise intensity [ 8 ], whereas at higher intensities, as our results showed that for COPD patients with a heavier GOLD grade, the expected ventilate ratio of maximum intensity exercise was lower. Therefore, due to the limitation of ventilatory function, it is necessary to rely more on the increased respiratory rate to meet metabolic requirements during certain intensity exercises.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This increase is accomplished by increases in both the tidal volume and breathing frequency. During low-to-moderate intensity exercise, both tidal volume and breathing frequency increase roughly in proportion to exercise intensity [ 8 ], whereas at higher intensities, as our results showed that for COPD patients with a heavier GOLD grade, the expected ventilate ratio of maximum intensity exercise was lower. Therefore, due to the limitation of ventilatory function, it is necessary to rely more on the increased respiratory rate to meet metabolic requirements during certain intensity exercises.…”
Section: Discussionmentioning
confidence: 78%
“…EqCO 2 (ventilatory equivalent for carbon dioxide) is a critical parameter in the CPET, which is calculated using the equation: VeqCO 2 = [V' E − ( d syst × RR)]/V' CO2 . EqCO 2 was the focus of this study because previous research demonstrated that this parameter is most useful in the diagnosis of dysfunctional breathing [ 8 ]. The increase in EqCO 2 indicates a decrease in ventilation efficiency [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Exercise-induced inappropriate hyperventilation is often diagnosed by an increased VE'/V'CO 2 slope on exercise or an increased ventilatory equivalent for CO 2 at different time points of exercise. 13,29 The increase in V'E/V'CO 2 slope (=863/(PaCO 2…”
Section: Discussionmentioning
confidence: 99%
“…Assessment at rest and during a provoked attack can help to identify the key indicators of BPD compared with normal breathing patterns (online supplemental table S2). 54 55 Typical features include a raised breathing frequency, predominantly apical/upper chest movement during respiration, asynchrony between upper and lower chest and excessive mouth breathing. There may also be frequent sighing, yawning or excessive accessory muscle use 49 53…”
Section: Section 3: Clinical Assessment and Management Of Commonly En...mentioning
confidence: 99%